DETERMINATION OF LEPTIN LEVEL WITH OTHER BIOCHEMICAL PARAMETERS IN TYPE 2 DIABETIC PATIENTS - Rafal Salam Kadhim (Scholar Express Journals, 2022)
An adipokine called leptin has been linked to pathways that affect the risk of diabetes mellitus and cardiovascular disease
Keywords: Leptin; T2DM; sandwich-based; ELISA